An Improved Approach to the Construct of Virtual Work Based On Estonian Service Sector Organisations - Õun, Kandela; Mihhailova, Gerda (Lithuanian Journal of Statistics, 2011)
The use of virtual teamwork is still a relatively new field for academic research and, even when researchedempirically, case study, interviewing or other small sample approaches are usually used. The aim of the paper is to present animproved construct of virtual work based on the Estonian service sector. The novel and theoretical contributions of the paperstem from presenting the improved approach in a new model that uses virtuality; a comparison is also made betweenvirtuality indices of easy and hard work. The empirical results presented in the paper are based on a sample of 781 respondentsfrom 93 service sector organisations. It was found that the improved index is linked to the initial index but differencesbetween respondent groups are clearer, and the improved index is much more user-friendly than the first virtuality index suggestedby the authors.